2012
DOI: 10.3892/or.2012.2070
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of HMGB1 in human liver cancer: Knockdown inhibits tumor growth and metastasis in vitro and in vivo

Abstract: The high-mobility group box 1 (HMGB1) signaling pathway plays a crucial role in tumorigenesis and progression of many malignant cancers. The present study aimed to investigate the expression and clinical significance of HMGB1 in human primary liver cancer, and further explore the molecular mechanisms of HMGB1 in tumor growth and metastasis. Forty cases of human liver cancer and normal liver tissues were collected. The expression of HMGB1 was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
2
38
1
Order By: Relevance
“…HMGB1 can activate caspase-1 and contribute to hepatocellular carcinoma invasion and metastasis [34]. Moreover, knockdown of HMGB1 has clinical significance that inhibits human liver cancer growth and metastasis [35]. Our results were consistent with the above reports and suggested that silencing of HMGB1 inhibited lung cancer migration and invasion.…”
Section: Discussionsupporting
confidence: 82%
“…HMGB1 can activate caspase-1 and contribute to hepatocellular carcinoma invasion and metastasis [34]. Moreover, knockdown of HMGB1 has clinical significance that inhibits human liver cancer growth and metastasis [35]. Our results were consistent with the above reports and suggested that silencing of HMGB1 inhibited lung cancer migration and invasion.…”
Section: Discussionsupporting
confidence: 82%
“…Extracellular HMGB1-induced chronic inflammation within the tumor microenvironment favors tumor survival, proliferation, metastasis and angiogenesis. Expression of HMGB1 is closely correlated with pathological grade and distant metastases of liver cancer, and knockdown of HMGB1 inhibits liver cancer growth and metastasis (75,76). Serum HMGB1 levels were significantly higher in HCC and HBV patients and were associated with clinicopathological features and outcome in HCC patients (64,77).…”
Section: Hmgb1 and Hepatocellular Carcinomamentioning
confidence: 95%
“…HMGB1 knockdown could suppress the ability of proliferation, migration, and invasion of HCC cells. HMGB1 overexpression could strengthen the ability of proliferation, migration, and invasion of HCC cells [15,22]. HMGB1 expression is significantly increased in laryngeal squamous cell carcinoma (LSCC) tissues, and HMGB1 overexpression is associated with a poorer prognosis [23].…”
Section: Introductionmentioning
confidence: 99%